PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KARYAWAN PADA PT. LUTVINDO WIJAYA PERKASA PEKANBARU - Jumelda, Zelvi; Suryalena, Suryalena (Jurnal Daya Saing, 2024)
Abstract: This research aims to analyze the effect of Reward (X1), Punishment (X2), on employee motivation (Y) at PT. Lutvindo Wijaya Perkasa Pekanbaru. The research method used in this study is a quantitative method by distributing questionnaires to employees of PT. Lutvindo Wijaya Perkasa. The data analysis technique used is multiple linear regression analysis using SPSS version 23. Based on the results of partial analysis, Reward has a positive effect on Employee Motivation at PT. Lutvindo Wijaya Perkasa, this is because the t-count obtained is greater than the value of the t-table (10,270>1,673). Punishment has a positive effect on Employee Motivation at PT. Lutvindo Wijaya Perkasa, this is because the t-count obtained is greater than the value of the t-table (12,123>1,673). While from the F test, it shows that there is a simultaneous relationship between variables X and Y because the F-count is greater than the value of the F-table (72.839>3.09). Keywords: Reward, Punishment, Motivation